Hyperbaena domingensis (DC.) Benth. (Menispermaceae), new records for the Atlantic Forest from northeastern Brazil - Amorim, Bruno S.; Araújo, Diogo [UNESP]; Alves, Marccus (My University, 2012)
Hyperbaena domingensis (DC.) Benth. has new records for the Atlantic Forest from northeastern Brazil. It is found in lowland coastal, sub-montane and montane remnants of Atlantic Forest as part of the forest canopy or drape dover edge shrubs and treelets. It can be recognized by the ovate to oblong leaves, spiciform or paniculiform inflorescence, dichlamydeous and 3-merous flowers, drupaceous and purple (at maturity) fruits, and horseshoe-shaped seeds. Comments, distribution map, and pictures are presented here. © 2012 Check List and Authors.
Keywords: Hyperbaena domingensis; Menispermaceae